Pengembangan Agrowisata Dengan Pendekatan Community Based Tourism (Studi Kasus : Di Paloh Naga, Denai Lama, Kecamatan Pantai Labu) - Hadziyah, Idzni; Siregar, Saparuddin; Nasution, Juliana (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine how the development of agro-tourism by using Community-Based Tourism approach, inhibiting factors, and business opportunities with the Paloh Naga Agro-Tourism.This study uses descriptive qualitative methods.Data collection is done by interview techniques, observation, documentation.The Data were analyzed qualitatively through indicators of planning, facilities and Infrastructure, Community Empowerment, customs, collaboration.The results showed that Paloh Naga Agro Tourism has good planning in terms of agro tourism development and promotion.Cooperation in the development of facilities and infrastructure needs to be improved, the facilities and infrastructure provided are further developed by adding photo spots and children's playgrounds. Community Empowerment, has formed a conscious mindset of tourism in the community. Customs continue to be preserved so that the existing culture is not lost to the Times and the welfare of the community increases. Collaboration is carried out with the state-owned enterprises, Tourism Office of Deli Serdang in terms of budget provision of infrastructure development. Constraints in the development of agro-tourism Paloh Naga lack of budget danauntuk planning in the future development and improvement of facilities and infrastructure. Business opportunities with the Paloh Naga agro tourism are very helpful to the community in increasing the economy.